Factors Influencing Caring Ability of Family Caregivers of Children with Cancer - Hafedh Owed, Hanan; Mohammed, Widad K. (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s): This study aimed to investigate factors influencing the caring ability of family caregivers of children with cancer based on caregiver sex, level of education, kinship to the child, and the child's sex.Methods: A descriptive study was conducted on 200 family caregivers of children with cancer, selected through non-probability (purposive) sampling technique in the Hematology and Oncology Center at Welfare Teaching Hospital from January 2nd, 2024, to March 27th, 2024. Data were collected using “the Caring Ability of Family Caregivers of Patients with Cancer Scale (CAFCPCS). Through a self-report method. Data were analysis using SPSS (version 24), employing descriptive and inferential statistics.Results: The study showed that there are several factors that affected the caring ability of family caregivers to their children with cancer, including the child’s kinship (p = .037), education level (p = .000), and monthly income (p = .003). Additionally, a significant correlation between the sex of caregivers and effective role play (p = .022), negative correlation between the education level of caregivers and the total score of caregiving abilities (p = .006).Conclusion: The study concludes that familial relationship, education level, and income significantly affect caregivers' abilities in caring for children with cancer. The sex of caregivers plays a role in their interactions with children with cancer, with mothers having greater knowledge and broader experience in caregiving.Recommendations: This study recommends that the Ministry of Health should encourage continuous family support, provide educational programs, and financial assistance to improve the abilities of family caregivers in dealing with their children with cancer. Mothers should be supported through women's workshops, and fathers' participation should be encouraged through specialized training programs.